2019
DOI: 10.5539/jas.v11n4p271
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity of Volatiles From Parents, Rootstock and Atemoya Hybrid

Abstract: Hybridization promotes the transfer of genetic material from parental species to the hybrid, which can be closely related to one of its parental species or present new features that provide them higher competitivity concerning other chemical phenotype comparing to its parents. On the other hand, grafting technique, in which occurs the combination between two species, also may lead to changes in the volatile profile of terpenes at the grafted plant. The objective of this research was to characterize the chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The cultivation of Annona emarginata revealed trans -caryophyllene, bicyclogermacrene, and γ-gurjunene, synthesized on the same route [68]. These substances have bactericidal activity [31,69,70] and may contribute to the defense of the species. We found a higher relative percentage of trans -caryophyllene when the plants are younger (150 DBT) and a higher relative percentage of bicyclogermacrene and γ-gurjunene when the plants are older (206 DBT).…”
Section: Discussionmentioning
confidence: 99%
“…The cultivation of Annona emarginata revealed trans -caryophyllene, bicyclogermacrene, and γ-gurjunene, synthesized on the same route [68]. These substances have bactericidal activity [31,69,70] and may contribute to the defense of the species. We found a higher relative percentage of trans -caryophyllene when the plants are younger (150 DBT) and a higher relative percentage of bicyclogermacrene and γ-gurjunene when the plants are older (206 DBT).…”
Section: Discussionmentioning
confidence: 99%
“…These authors found a majority percentage of sesquiterpenes in young plants of A. emarginata ‘terra‐fria’ – collected in 2012 –, with the major substance being the compound E‐caryophyllene. Recently, Campos et al [25] . observed that sesquiterpenes (particularly caryophyllene), even with intraspecific variations, remain as the major components (up to 80 %) in plants grown with different levels of nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…The capture of leaf volatiles (0.250 g) was carried out using a solid phase microextraction in headspace mode (HS‐SPME), with an SPME Fiber Assembly [75 μm of carboxen/polydimethylsiloxane (CAR/PDMS)], as described by Campos et al [25] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations